Managing workforce diversity: an Islamic perspective - Muhtada, Dani (Indonesian Journal of Islam and Muslim Societies, 2012)
Workforce diversity is an inevitable phenomenon of the day. Diversity managementis then developed in response to this reality. The discourse has been widelyimplemented in many western countries and some other countries across theworld. Yet, it does not sound loudly in the Muslim countries. The objective of thispaper is to discover Islamic perspective of workforce diversity management. Theresults show that pluralism and multiculturalism values are strongly promoted inIslamic teaching. Although, some conceptual problems regarding conservativeviews on diversity might constrain diversity workforce management, but a strategicsolution to this issue is not impossible. This paper basically favors the idea ofimplementing the Lewin-Schein change model (i.e., unfreezing â change [moving]â refreezing) for managing diversity in the Muslim society context but with amore focus given to the substantive aspects of diversity management (i.e., elaboratingIslamic values on diversity). The role of such qualified Islamic scholars iscrucial in this regard.Keragaman sumber daya manusia di tempat kerja adalah sebuah fenomena yangtidak terhindarkan dewasa ini. Karena itu, mengelola keragaman secara professionaladalah sebuah keniscayaan. Meskipun diskursus tentang pengelolaankeragaman di tempat kerja bukanlah hal yang baru di dunia Barat, namun dinegara-negara berpenduduk mayoritas muslim praktik dan wacana tentang hal tersebut masih kurang mendapatkan perhatian. Paper ini bertujuan untukmenawarkan konsep manajemen keragaman di tempat kerja dalam perspektifIslam. Paper ini menggarisbawahi bahwa multikulturalisme sesungguhnya memilikitempat yang signifikan dala ajaran Islam. Kendati ada ada persoalan konseptualberkaitan pandangan-pandangan konservatif tentang pluralism danmulrikulturalisme, yang nota bene dapat menghambat efektivitas manajemenkeragaman di dunia Islam, namun persoalan ini bukan tidak dapat dipecahkan.Paper ini berpendapat bahwa framework yang ditawarkan oleh Lewin-Scheintentang pengelolaan keragaman dapat diadaptasi dalam konteks dunia Islamdengan mengelaborasi konsep-konsep ajaran Islam tentang keragaman.